Tanfīż Tarīqah Tamṡīl al-Adawār (Role Playing) li Māddah al-Muṭāla’ah bi al-Ma’had: Application of the Role-Playing Method to Muṭāla’ah Material in Islamic Boarding Schools - bin Zaid, Abdul Hafidz; Sudarsono, Ahmad Luqman; Amalia, Rizki (Study Program of Arabic Language Teaching, 2023)
Role-playing is one of the methods in classroom classroom learning that will create a pleasant classroom atmosphere, enhance active learning of students’ lessons, and strengthen students’ learning outcomes. This research will study class action using the role-playing method in class 3 intensive PMDG Putri 1 Mantingan, Ngawi, East Java. Therefore, the study aims to 1) expose the effectiveness of the implementation of the role playing method in enhancing the active learning of the lessons Muthola'ah students Class 3 intensive PMDG Putri 1 year teachings 2018-2019 AD, and 2) display the effectiveness of the implementation of role playing methods in enhancing the learning outcomes of students' Muthola'ah Class 3 intensive at Darussalam Gontor Putri 1 Islamic Boarding School the school year 2018-2019. This research is a qualitative descriptive action class (PTK) study implemented in the intensive 3 class of 45 students in PMDG Putri Campus 1 school year 2018/2019. Class action research is carried out in two cycles: planning, action, observation, and reflection. The results of this research show that (1) the application of the role-playing method can improve students' learning activity; namely, in the first cycle of activation, students reach 48% and increase to 53% in the second cycle. (2) The application of the role-playing method Playing can improve students' learning outcomes, i.e., students' learning results in the first cycle reach 82% and increase to 84% in the second cycle. Therefore, researchers hope that all teacher councils will give more attention to the learning methods that will be applied to a lesson so that they will create a conducive and effective learning environment.